Work satisfaction and customer satisfaction in the atention provide for Arequipa Departamental Club - Pino Apablaza, Fernando (2020)
The investigation determined the influence between the labor satisfaction levels and the satisfaction customers levels, in relation to quality of services provides for the organization. The investigation started in the first trimester of 2018 and finished the second trimester in the same year in district of Jesus Maria, province of Lima. The kind of investigation is correlation. For measure the satisfaction levels in both groups, was used two instruments to collect data. In the hypothesis proof, was used the inverse proof, using the Pearson coefficient and the Anova to analyze the difference between variances. Finally the null hypothesis was rejected and prove the existence of the positive relation between the satisfaction levels of employees and customers. Also evidenced a significant diferences between the statistics medias in both groups, after and before to the application of improvement program about the life worker quality.